Sejarah Perkembangan Esport Indonesia Kabupaten Kuningan - asep nurali ali (Indonesian Journal of Education Teaching and Learning (IJETL), 2024)
This research aims to determine the history of the development of Indonesian Esports in Kuningan district. The type of research used is descriptive qualitative. The samples in this research were the Chairman of PBESI Kuningan, the PBESI Kuningan Management and 10 Esports teams in Kuningan Regency. The method used is a qualitative descriptive method by collecting data through observation, interviews and documentation, while the data analysis technique uses 3 methods of analysis, namely data reduction, data presentation, verification and conclusions. The results of the research from 10 teams, there were 7 teams who knew the history of PBESI Kuningan, 10 teams followed the development of Esports and knew that there were quite a lot of fans of Esports in Kuningan Regency, of the 10 teams there were 8 teams who had won tournaments in Kuningan Regency, all respondents knew one of these games. 10 teams are actively competing in Kuningan Regency, knowing that the role of ESI is very important for Esports in Kuningan Regency. The history of the formation of PBESI Kuningan in 2019 coincided with the Asian Games exhibition which was then inaugurated simultaneously in Bandung. The development of Esports is considered very good because there are lots of enthusiasts in Kuningan Regency, there are 2 games that are actively competing in Kuningan Regency at the moment, namely Free Fire and Mobile legends.